Students’ Perceptions on Mobile-Assisted Language Learning (MALL) in EFL Class: An Overview of Altissia Usage - Rizky Vita Losi (LPPM Universitas Trunojoyo Madura, 2022)
Previous research has revealed that MALL are becoming widely used since it can increase students’ knowledge and skills in English language learning. This study aimed to investigate students’ perceptions on MALL, particularly Altissia, in EFL class. Most of students did not use or access Altissia during the learning process was becoming one of the problems that leads to the low ability in students’ English skills. In total, thirty students answered a questionnaire survey after experiencing Altissia in their learning activity. The findings revealed that the students’ agreement to the positive perceptions were showed in the questionnaire prevailed over their disagreement or neutral responses. Altissia contributed great impact on their listening skills and vocabulary knowledge. Altissia also supported them to enhance their motivation and interest to keep learning English. Students felt excited in learning new levels in different topics on Altissia. Students could practice to communicate their English skills more often after learning with Altissia. On the other hand, as the findings also indicated the students did not get any notification related to the study time and they did not experience writing activity on Altissia. Moreover, Altissia can be an alternative learning media that can improve students’ skills in their EFL class.